Exploring the Intersection of Spirituality and Marital Satisfaction: Insights from Islamic Families - Aziz, Rahmat; Mangestuti, Retno (Proceedings Conference Psychology and Flourishing Humanity; Vol 1 No 1 (2024): Proceedings Conference on Psychology and Flourishing Humanity, 2025)
The article explores the intricate dimensions of marital satisfaction, proposing that a fulfilling partnership hinges on the mutual dedication of both spouses to foster spiritual growth. The research encompassed 410 participants from Islamic families, equally divided among husbands and wives, across seven cities in East Java. Data was gathered using the Marital Satisfaction Scale and the Daily Spiritual Experience Scale. Through comprehensive descriptive and regression analyses, a pronounced correlation between spiritual engagement and marital satisfaction was discovered, with spirituality accounting for 24% of the variance in happiness, evidenced by a significant R value of .489 and an R² of .240. These findings underscore the vital influence of spirituality in enhancing the quality of marriage and advocate for the integration of spiritual practices into daily life as a fundamental strategy for improving marital fulfillment. This study contributes a meaningful insight to academic discussions on family and relationships, offering a robust foundation for further research and practical application in marriage counseling and relationship enhancement programs.